The Prospect of Hydrogen Storage Using Liquid Organic Hydrogen Carriers - Modisha, Phillimon M.; Ouma, Cecil N.M.; Garidzirai, Rudaviro; Wasserscheid, Peter; Bessarabov, Dmitri (Energy & Fuels, 2019)
Reducing CO 2 emissions is an urgent global priority. The enforcement of a CO 2 tax, stringent regulations, and investment in renewables are some of the mitigation strategies currently in place. For a smooth transition to renewable energy, the energy storage issue must be addressed decisively. Hydrogen is regarded as a clean energy carrier; however, its low density at ambient conditions makes its storage challenging. The storage of hydrogen in liquid organic hydrogen carriers (LOHC) systems has numerous advantages over conventional storage systems. Most importantly, hydrogen storage and transport in the form of LOHC systems enables the use of the existing infrastructure for fuel. From a thermodynamic point of view, hydrogen storage in LOHC systems requires an exothermic hydrogenation step and an endothermic dehydrogenation step. Interestingly, hydrogenation and dehydrogenation can be carried out at the same temperature level. Under high hydrogen pressures (typically above 20 bar as provided from electrolysis or methane reforming), LOHC charging occurs and catalytic hydrogenation takes place. Under low hydrogen pressures (typically below 5 bar), hydrogen release from the LOHC system takes place. Hydrogen release from charged LOHC systems is always in conflict between highly power-dense hydrogen production and LOHC stability over many charging/discharging cycles. We therefore discuss the role of different catalyst materials on hydrogen productivity and LOHC stability. The use of density functional theory techniques to determine adsorption energies and to identify rate-determining steps in the LOHC conversion processes is also described. Furthermore, the performance of a LOHC dehydrogenation unit is strongly dependent on the applied reactor configuration. Industrial implementation of the LOHC technology has started but is still in an early stage. Related to this, we have identified promising application scenarios for the South African energy market.
CRIS-Team Scopus Importer:2019-05-09